The Role of Bacteria in the Termites Intestine Macrotermes gilvus Hagen as a Biological Agent in the Degradation of Medical Mask Waste - Niken Subekti; Retno Wulandari (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
The use of disposable medical masks during the Covid-19 pandemic can cause solid waste problems in the environment. The subterranean termite Macrotermes gilvus Hagen has the potential to degrade medical mask waste due to the presence of microorganisms in its intestines. The purpose of this study was to analyze the effect of adding starter bacteria from the intestine of the subterranean termite M. gilvus Hagen and the most optimal composting time in the degradation of medical mask waste according to SNI standards based on physical properties (color, smell, and texture), chemical properties (C-Organic content, N content, and C/N) compost. The results showed that the addition of bacterial starter from the subterranean termite intestine M. gilvus Hagen with a concentration of 50% and a composting time of 5 weeks gave the best compost yield according to SNI No. 19-7030-2004 because it has a dark brown color, crumb texture, smells like soil, 20.22% C-Organic content, 1.35% total N content, and 15.14% C/N content. This research can be recommended as an alternative solution for waste management using biological agents.